A abordagem fractal em Geociencias - H. Christofoletti, A. L.; Christofoletti, A. (My University, 1995)
This is a synthesis of the use of fractal approaches in geosciences. It presents references and a list of publications, taking into account sectors of many fields, including geophysics, petrology, mineralogy, sedimentology, tectonics, meteorology, climatology, geomorphology, hydrogeology, oceanography, geomechanics, geochemistry and soil studies. -English summary
Fractal approaches in geosciences
Keywords: earth science; Earth science; fractal analysis